Extracellular vesicles derived from gut microbiota in inflammatory bowel disease and colorectal cancer - Alberti, Giusi; Mazzola, Margherita; Gagliardo, Carola; Pitruzzella, Alessandro; Fucarini, Alberto; Giammanco, Marco; Tomasello, Giovanni; Carini, Francesco (Biomedical papers, 2021)
The human gut microbiome encompasses inter alia, the myriad bacterial species that create the optimal host-microorganism balance essential for normal metabolic and immune function. Various lines of evidence suggest that dysregulation of the microbiota-host interaction is linked to pathologies such as inflammatory bowel disease (IBD) and colorectal cancer (CRC). Extracellular vesicles (EVs), found in virtually all body fluids and produced by both eukaryotic cells and bacteria are involved in cell-cell communication and crosstalk mechanisms, such as the immune response, barrier function and intestinal flora. This review highlights advancements in knowledge of the functional role that EVs may have in IBD and CRC, and discusses the possible use of EVs derived from intestinal microbiota in therapeutic strategies for treating these conditions.
Keywords: extracellular vesicles; gut microbiota; inflammatory bowel disease; colorectal cancer